Artificial Intelligence Use in Daily and Professional Life among Pediatric Surgeons in India: A Roadmap for Adoption Based on Online Survey Results - Ankur Mandelia; Vinayak S. Rengan; Alish Rajesh Mehta; Aseesh Varma Vankam; Ramesh Babu; Sumitra Kumar Biswas; Vikesh Agrawal (Journal of Indian Association of Pediatric Surgeons)
Background: Artificial intelligence (AI) is transforming the various domains of medicine, including pediatric surgery, where precision and timely decision-making are critical. However, the real-world integration of AI in pediatric surgery, particularly in low- and middle-income countries such as India, remains underexplored. We propose a roadmap for the adoption of AI based on our survey results for Indian Association of Pediatric Surgeons (IAPS). Objective: This survey aimed to evaluate the awareness, utilization, and perspectives of pediatric surgeons in India regarding AI in both professional and personal settings, as well as to identify barriers and opportunities for its integration into clinical practice. Methodology: A cross-sectional survey was conducted among the members of the IAPS, utilizing a structured online questionnaire. Quantitative data were analyzed using the descriptive statistics and Chi-square tests, whereas qualitative responses were thematically analyzed. Results: A total of 74 pediatric surgeons participated in the survey. While 60.8% were somewhat familiar with AI, only 47.3% used AI in their clinical practice, primarily for diagnostic imaging (31.1%) and administrative tasks (23%). Perceived benefits included enhanced diagnostic accuracy (45.9%) and improved surgical care (37.8%), yet barriers such as data privacy (39.2%) and concerns over reliability (51.4%) were prevalent. Personal AI adoption was high (70.3%), with virtual assistants and health-tracking apps being most common. Additionally, 86.4% of respondents anticipated AI becoming integral to pediatric surgery within the next decade. Conclusion: Despite limited clinical adoption, there is strong interest among pediatric surgeons in India for AI-focused training and integration. Addressing barriers such as ethical concerns, data privacy, and cost could catalyze AI’s potential to revolutionize pediatric surgical care. Our roadmap addressing these challenges through targeted education, ethical guidelines, and better integration strategies will be essential for harnessing AI’s full potential in pediatric surgery.